Protective effects of aqueous garlic extract in reducing water avoidance stress-induced degeneration of the stomach, ileum, and liver: Morphological and biochemical study - ERCAN, FERİHA (SPRINGER, 2007)
We investigated the effect of aqueous garlic extract (AGE) on water avoidance stress (WAS)-induced degeneration of the gastric and ileal mucosa and liver parenchyma. Wistar albino rats were exposed to WAS (WAS group) for 5 days. After exposure of the animals to WAS, a 1 ml/kg aqueous garlic extract (AGE) was injected i.p. (WAS+AGE group). The stomach, ileum, and liver samples were investigated under light microscope for general morphology. Topography of gastric and ileal mucosa was investigated by scanning electron microscopy, and hepatocyte ultastructure by transmission electron micsroscopy. Malondialdehyde (MDA) and glutathione (GSH) levels of all tissues were also determined. In the WAS group, the epithelium of the stomach showed ulceration in some areas, dilatations of the gastric glands, and degeneration of gastric glandular cells. Severe vascular congestion and degeneration of ileal epithelium were observed. Prominent vascular congestion and dilated sinusoids, activated Kupffer cells with prominent morphology, dilated granular endoplasmic reticulum membranes, and focal picnotic nuclei were observed in liver parenchyma. AGE treatment reduced the degeneration of the gastric and ileal mucosa and liver parenchyma. Increased MDA levels and decreased GSH levels in the WAS group were reversed to control values after AGE treatment. Based on these results, AGE treatment significantly prevented WAS-induced degeneration in both morphology and biochemistry of gastrointestinal mucosa and liver parenchyma due to its potent free radical scavenging and antioxidant properties.
Keywords: water avoidance stress; stomach; ileum; liver; morphology; lipid peroxidation; glutathione; aqueous garlic extract; OXYGEN FREE-RADICALS; MUCOSAL BLOOD-FLOW; OXIDATIVE STRESS; COLD-RESTRAINT; EPITHELIAL BARRIER; GASTRIC-MOTILITY; S-ALLYLCYSTEINE; RAT; DAMAGE; ANTIOXIDANT